2022
DOI: 10.35877/454ri.eduline927
|View full text |Cite
|
Sign up to set email alerts
|

Post COVID-19 Learning Adaptation: Teachers’ Strategies and Innovations in Teaching English in the Post Pandemic

Abstract: Limited Face-to-face Learning is a government initiative program to solve the problem of learning loss during online learning in the Covid 19 outbreaks by implementing strict health protocol procedures to prioritize student safety. This research aimed to describe the preparation for learning in the new normal period, explore the practice of limited face to face learning in English subject, and teachers’ strategies in teaching English in the post pandemic. This research used a descriptive qualitative method wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In addition, students may face psychological burdens in the online environment. Wirawati et al (2022) point out that students may experience increased stress, anxiety, or a sense of detachment in online learning. --------------------------------------------------------------------------------------------------------------------------------------- Furthermore, Davies and Graff (2005) found that the absence of face-to-face interactions and immediate feedback in online learning environments can hinder students' academic performance and learning progress.…”
Section: Febriyanti (2023)mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, students may face psychological burdens in the online environment. Wirawati et al (2022) point out that students may experience increased stress, anxiety, or a sense of detachment in online learning. --------------------------------------------------------------------------------------------------------------------------------------- Furthermore, Davies and Graff (2005) found that the absence of face-to-face interactions and immediate feedback in online learning environments can hinder students' academic performance and learning progress.…”
Section: Febriyanti (2023)mentioning
confidence: 99%
“…Rianto (2021) also emphasizes that students' social and academic development may be compromised online, as they miss out on collaborative learning and social interactions inherent in traditional classrooms. The characteristics of students and the learning environment can also contribute to the challenges faced in online learning (Wirawati et al, 2022). Technological limitations, distractions at home, and difficulties in self-regulation and time management can further impede the learning process and hinder student success.…”
Section: Febriyanti (2023)mentioning
confidence: 99%
See 1 more Smart Citation
“…After the COVID-19 Pandemic, teachers and students often face several obstacles. (Wirawati et al, 2022) The process of shifting teaching and learning from offline to online, and then back again, necessitates adaptation and modifications, known as the new normal era. (Munawaroh & Nurmalasari, 2021) As stated, alterations within educational institutions impact the comprehension of the procedure in various aspects, including the standard of graduates.…”
Section: Introductionmentioning
confidence: 99%
“…Then, as time went on and the number of positive cases of Covid-19 in Indonesia decreased, the government initiate program known as Limited Face-to-Face Learning that implemented with the aim of overcoming the problem of learning loss during online learning the Covid-19 pandemic. According to Wirawati et al (2022), the process of learning English, in general, is going well and is presented through some exciting strategies and fun methods, although there are still some obstacles. According to Manggoa (2020) some of the most apparent challenges in teaching during the Covid-19 epidemic include those caused by technology and learning media, teacher inexperience, insufficient infrastructure and facilities, methodological issues, and a lack of human resources.…”
Section: Introductionmentioning
confidence: 99%